Un testimonio tardío de ludi theatrales en Hispania - Jiménez Sánchez, Juan Antonio (Gerión. Revista de Historia Antigua, 2003)
It is said that a letter written by The Visigothic king Sisebutus (AD 612-621) and addressed to Eusebius, the metropolitan bishop of Tarragona, could give us the later date for the exhibition of ludi theatrales at Hispania (AD 614/620). Howewer, this does not mean that we must rely on this document to date the last performance at Hispania of another king of games. Maybe these shows that the epistle mentions were private exhibitions. This is a logical conclussion if we remember the fact that some ecclesiastical council canons forbade bishops to attend those entertainments.